Smartphone fluorescence imager for quantitative dosimetry of protoporphyrin-IX-based photodynamic therapy in skin - Ruiz, Alberto J. (J Biomed Opt, 2019)
Significance: While clinical treatment of actinic keratosis by photodynamic therapy (PDT) is widely practiced, there is a well-known variability in response, primarily caused by heterogeneous accumulation of the photosensitizer protoporphyrin IX (PpIX) between patients and between lesions, but measurement of this is rarely done. Aim: Develop a smartphone-based fluorescence imager for simple quantitative photography of the lesions and their PpIX levels that can be used in a new clinical workflow to guide the reliability of aminolevulinic acid (ALA) application for improved lesion clearance. Approach: The smartphone fluorescence imager uses an iPhone and a custom iOS application for image acquisition, a 3D-printed base for measurement standardization, an emission filter for PpIX fluorescence isolation, and a 405-nm LED ring for optical excitation. System performance was tested to ensure measurement reproducibility and the ability to capture photosensitizer accumulation and photobleaching in pre-clinical and clinical settings. Results: PpIX fluorescence signal from tissue-simulating phantoms showed linear sensitivity in the 0.01 to 2.0 μM range. Murine studies with Ameluz(®) aminolevulinic acid (ALA) gel and initial human testing with Levulan(®) ALA cream verified that in-vivo imaging was feasible, including that PpIX production over 1 h is easily captured and that photobleaching from the light treatment could be quantified. Conclusions: The presented device is the first quantitative wide-field fluorescence imaging system for PDT dosimetry designed for clinical skin use and for maximal ease of translation into clinical workflow. The results lay the foundation for using the system in clinical studies to establish treatment thresholds for the individualization of PDT treatment.